Psychiatric Disorders and Sociodemographic Characteristics of Sexually Abused Children and Adolescents - Koçak, Uğur; Alpaslan, Ahmet Hamdi (The Bulletin of Legal Medicine, 2015)
Aim: In this study, it was aimed to determine socio-demographic characteristics and psychiatric diagnoses of sexually abused children and adolescents. Materials and Methods: The data of the sexually abused children and adolescents (n=158) who were referred to the Department of Child and Adolescent Psychiatry for a forensic report between October 2012 and May 2014 were examined retrospectively. The socio-demographic characteristics, psychiatric diagnoses, mental statuses, juridical requests, and abuser-victim relationships of the forensic cases were collected from the outpatient medical records. The cases were diagnosed using DSM-IV TR criteria. Results: Of the 158 cases included in the study, 17.7% (n=28) was male and 82.3% (n=130) was female. Their age varied between 6 and 18 years, with a mean of 13.94 (sd±2.56) years. Vaginal penetration was the most reported type of abuse with a rate of 32.5%, followed by sexual touching (29.9%), anal penetration (22.3%) and the others. When the psychiatric diagnoses of the cases were analyzed, post traumatic stress disorder (PTSD) was the most common diagnosis with a rate of 24.1%, followed by depressive disorder (20.9%), and acute stress disorder (19.0%) respectively, 36.1% of the cases had no psychiatric diagnosis. Conclusion: The incidence rate of child sexual abuse is increasing alarmingly in our country such as in the world. Our findings suggest that broader interdisciplinary research is needed to reveal child and adolescent sexual abuse. Keywords: child, adolescent, sexual abuse, sociodemographic characteristics.